A Study of the Curriculum and Learning Management Competency through PBL of the Students in Bachelor of Education Program - Phonnong, Isara; Pinthuto, Pradabsri (Ratchaphruek Journal, 2022)
This research was to study the curriculum and learning management competency by using problem based learning for the pre-service teachers. The objectives were: 1) To compare the competency between the pre-test and post-test score; and 2) To compare the competency between post-test score and 70% of standard criterion. The sample consisted of 32 second-year pre-service teachers majoring in General Science, Faculty of Education, Nakhon Ratchasima Rajabhat University, in the first semester, 2021 academic year. They were selected by using the simple random sampling method. The research tools were the lesson plan and competency test. The collective data were analyzed by means, standard deviation, percentage, t-test for dependent, and t-test for one sample. The results showed that: the post-test’s mean score were significantly higher than pre-test’s mean score at .05, and the post-test’s mean score was lower than the 70% of standard criterion.